Self-Efficacy and the Sense of Coherence: Narrative Review and a Conceptual Synthesis. (2009) - Posadzki, Paul; Glass, Nel
Abstract : In this study, the authors develop an exploratory synthesis of two major health concepts: Antonovsky's sense of coherence and Bandura's beliefs in one's own efficacy. Reinterpretation of each study in the light of the other can lead to greater conceptual development and expand existing knowledge. The mutual themes are presented with an explanation of their contribution to broader conceptual discussions. The existence of some similarities between the two concepts is suggested. Researchers can obtain valuable and additional arguments through cross-fertilization of ideas across presented studies united by shared assumptions. Further research is recommended among various age groups and social backgrounds in order to verify the possible benefits of such theoretical development. Theoretical and practical implications of such a synthesis are presented.